A Holistic Approach to Evaluating Wardah Cosmetics E-PR Impact on Brand Perception - Amora Siregar; Devani Mutia Widiastuty (International Institute for Advanced Science & Technology (IIAST), 2023)
In the rapidly developing digital era, the role of internet media, especially through Cyber Public Relations (E-PR) practices, has become crucial for companies in building brand images and expanding market share. This study explores the influence of E-PR on the brand image of Wardah Cosmetics, a leading cosmetics company. Through a mixed method approach, this research explores the impact of E-PR on consumer perceptions of the Wardah brand. Data was collected through quantitative analysis which was then deepened with qualitative analysis. The research results show that Wardah's E-PR activities have a significant influence on its brand image. The main contribution of this research is to open new insights regarding Cyber Public Relations strategies in the context of the cosmetics industry. The finding that online search sites and social media play a central role in strengthening brand image suggests a new direction for PR practitioners. The implications of this research include strategic guidance for other cosmetic companies in utilizing E-PR effectively. The novelty of this research lies in its holistic approach that combines quantitative and qualitative analysis, opening the door for in-depth research on the relationship between E-PR and consumer perceptions. Thus, this research enriches the public relations literature and provides a basis for the future development of more sophisticated and targeted E-PR practices.